Quantitative assessment of blood-brain barrier permeability in multiple sclerosis using 68-Ga-EDTA and positron emission tomography. Issue 8 (August 1988) - Pozzilli, C; Bernardi, S; Mansi, L; Picozzi, P; Iannotti, F; Alfano, B; Bozzao, L; Lenzi, G L; Salvatore, M; Conforti, P
Abstract : Fifteen patients with definite multiple sclerosis were examined with high volume delayed (HVD) CT scan and positron emission tomography (PET) using 68-Ga-EDTA as a tracer. The passage of 68-Ga-EDTA across the blood-brain barrier (BBB) was measured by using multiple graphical analysis. This method permits the simultaneous calculation of a blood to brain influx constant Ki (ml/g-1 min-1) and of the plasma volume Vp (ml/g-1). Focal areas of abnormal CT enhancement and pathological accumulation of 68-Ga-EDTA were visualised in four patients who were all examined during a clinical exacerbation of the disease. The mean Ki value measured in these areas was 12.5, SD 3.4 indicating a moderate but significant increase of BBB permeability compared with the value found in normal tissue (3.2, SD 0.9). No parallel increase in Vp values was found in these pathological areas. Quantitative data obtained with PET seems to provide further insight into the study of BBB function in multiple sclerosis.